Experimental investigation of blending phenomena in intergranular zones of recycled asphalt mixtures using customized infrared imaging and stage extraction methods. (20th July 2019) - Vassaux, S.; Gaudefroy, V.; Boulangé, L.; Pévère, A.; Michelet, A.; Barragan-Montero, V.; Mouillet, V.
Graphical abstract: Highlights: A statistical infrared chemomap method has been customized on recycled asphalt mixtures. The solvent-free chemomap method is highly sensitive to refine mixing and blending phenomena. The manufacturing process determines the way reclaimed asphalt affects the binder blending. Remobilization, homogeneity and oxidation are complementary to assess the binder blending. Abstract: In the recycling road industry, a fundamental knowledge of blending mechanisms between the aged and virgin binders is necessary. An infrared imaging methodology is customized to assess the blending in different recycled asphalt mixtures. Obtained results are compared to those of another stage extraction technique. Both methods show that RA materials behave differently according to the process. Furthermore, the infrared methodology is highly-sensitive to understand blending scenarii: as remobilization is lower in warm-mix processes, the intergranular zone appears less oxidized and more homogeneous. This study encourages mix designers to optimize current blending laws with the introduction of a remobilization degree.